Supplemented and Ï€-Projective Semimodules - Altaee, Muna M. T.; Alhossaini, Asaad M. A. (Iraqi Journal of Science, 2020)
In modules there is a relation between supplemented and Ï€-projective semimodules. This relation was introduced, explained and investigated by many authors. This research will firstly introduce a concept of "supplement subsemimodule" analogues to the case in modules: a subsemimodule Y of a semimodule W is said to be supplement of a subsemimodule X if it is minimal with the property X+Y=W. A subsemimodule Y is called a supplement subsemimodule if it is a supplement of some subsemimodule of W. Then, the concept of supplemented semimodule will be defined as follows: an S-semimodule W is said to be supplemented if every subsemimodule of W is a supplement. We also review other types of supplemented semimodules. Previously, the concept of Ï€-projective semimodule was introduced. The main goal of the present study is to explain the relation between the two concepts, supplemented semimodule and Ï€-projective semimodules, and prove these relations by many results.